Science problem solving in elementary schools through the application of project-based learning - Roosyanti, Anna; Suryarini, Diah Yovita (Journal of Research in Instructional, 2024)
This study focuses on the lack of widespread training in problem-solving skills among students. This research aims to determine the application of project-based learning (PjBL) to improve students' science problem-solving skills in elementary schools. The study used a quantitative method. The subjects of the study were 21 students of grade III elementary school. The data analysis results show that overall learning was successful, with students achieving an average learning achievement of 80.55% in the very good category. Teachers achieved an average learning achievement of 86.46% in the very good category. The student's learning response was categorized as very good, achieving a percentage of 92.38%. The implementation of learning resulted in a significant increase of 33.86% in student scores. Accordingly, it can be concluded that the problem-solving skills of elementary school students increase after the application of PjBL. In general, the implementation of learning is carried out well, with good categories of teacher and student learning achievements. Students’ responses to the learning implementation met very good criteria.